Enjeux de pouvoir, pouvoir en jeu et institutionnalisation de la société secrète abakuá à la Havane - Géraldine Morel-Baró (EchoGéo)
The abakuá masculine secret society is a religious practice localized at the west of the cuban island. Black masonery or caritative brotherhood, this organisation always had ambiguous and conflictuous relationships with the political power. How complex is her relationships with actual socialist government and the struggle for an official recognition? This new statute ask about power in urban space in general and about religious practices into the revolutionary process.